Development of Smart Circuit Breakers to Prevent Fire from Short Circuit Current - Khummanee, Suchart; Artcharoen, Aekkarach; Chanobrum, Peerawat (Journal of Applied Informatics and Technology, 2021)
According to the survey results, the top three causes of fire in Thailand: 1) garbage and hay burning, 2) short-circuit current, and 3) misuse of fuel. In this paper, a prototype innovation for reducing the fire problem caused by short-circuit current has been developed, called Smart Breaker. It has outstanding qualities, including the ability to see (IR and DHT11 Sensor), smell (MQ-2) and sense (PZEM 400T) the cause of a fire. It can also report anomalies from fire detections to property owners' smartphones to let them know before the damage escalates. The smart breaker applies Internet of Things technology (IoT) to develop the prototype. The result obtained from testing the prototype fire detection device shows that the fire detection accuracy is accurate ( = 3.42) or 68.4 percent.